The Preschool Classroom Management and Inclusion in Turkey - Sucuoglu, Nimet Bulbin; Bayrakli, Hatice; Karasu, Fadime Iscen; Demir, Seyda (Anadolu Univ, 2017)
This study evaluates classroom management of preschool teachers by using the data collected from 147 teachers who have and do not have children with disabilities in their classrooms. The Turkish Form of the Teacher Strategies Questionnaire (TSQ-T) was used for gathering data based on teachers' opinions of the classroom management strategies that they use. The authors found that the TSQ-T is a reliable instrument for investigating preschool classroom management, and that the frequency and usefulness scores regarding the management strategies of the teachers who have and do not have children with disabilities in their classrooms are similar, except for the fact that the inclusive classroom teachers view the negative strategies as being less useful than the other group of teachers. In addition, the Turkish teachers have almost the highest scores on their current and future confidence in being able to deal with problems. The authors discussed the results in terms of the content of the pre-service and in-service classroom management courses and practicums related to management skills of the preschool teachers and the teacher candidates.
Keywords: Preschool Teachers; Classroom Management; Inclusion